2021
DOI: 10.1101/2021.03.17.435876
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

REST is a major negative regulator of endocrine differentiation during pancreas organogenesis

Abstract: SUMMARYUnderstanding genomic regulatory mechanisms of pancreas differentiation is relevant to the pathophysiology of diabetes mellitus, and to the development of replacement therapies. Numerous transcription factors promote β cell differentiation, although less is known about negative regulators. Earlier epigenomic studies suggested that the transcriptional repressor REST could be a suppressor of endocrine gene programs in the embryonic pancreas. However, pancreatic Rest knock-out mice failed to show increased… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 79 publications
(132 reference statements)
0
3
0
Order By: Relevance
“…We observed that nearly 65% of ins + cells in the secondary islets (residing along the large ducts) can be lineage traced (Figure 3E-H and Figure EV6D). Furthermore, we performed short-term lineage tracing experiments in the presence of a Notch inhibitor (LY411575) or a REST inhibitor (X5050), as previous studies described (29, 47), to demonstrate the neogenic potential of nkx6.1 + intrapancreatic ductal cells in zebrafish larvae (Figure EV5). We found that more than 80% of ins + cells and around 75% of gcg + cells in the pancreatic tail can be lineage traced after three-day treatment (3-6 dpf) with LY411575 and X5050, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We observed that nearly 65% of ins + cells in the secondary islets (residing along the large ducts) can be lineage traced (Figure 3E-H and Figure EV6D). Furthermore, we performed short-term lineage tracing experiments in the presence of a Notch inhibitor (LY411575) or a REST inhibitor (X5050), as previous studies described (29, 47), to demonstrate the neogenic potential of nkx6.1 + intrapancreatic ductal cells in zebrafish larvae (Figure EV5). We found that more than 80% of ins + cells and around 75% of gcg + cells in the pancreatic tail can be lineage traced after three-day treatment (3-6 dpf) with LY411575 and X5050, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Rest is a master regulator of neurogenesis and has been previously described to inhibit direct reprogramming of pancreatic exocrine to endocrine cells by inhibiting the binding of Pdx1 to key endocrine differentiation-related genes [59]. In addition, loss of Rest results in increased generation of pancreatic endocrine cells during development [60, 61]. Nfib belongs to the Nuclear Factor I protein family, of which another member, Nfia , plays a role in the induction of EP cell fate [62].…”
Section: Resultsmentioning
confidence: 99%
“…Pancreatic beta cells and neuronal cells share similar functions. Repressor element-1 silencing transcription factor (Rest) is important for the terminal differentiation of pancreatic beta cells and neuronal cells through the regulation of neuronal and pancreatic endocrine gene 1 2 3 4 5 . Generally, the Rest gene is not expressed in mature pancreatic beta cells and beta cell line 6 and is classified as a disallowed gene in pancreatic beta cells 7 .…”
Section: Introductionmentioning
confidence: 99%